Degassing of a decompressed flowing liquid under hypergravity conditions. (June 2019) - Oikonomidou, Ourania; Evgenidis, Sotiris P.; Schwarz, Christian J.; van Loon, Jack J.W.A.; Kostoglou, Margaritis; Karapantsios, Thodoris D.
Highlights: Bubbles buoyant velocity increases with hypergravity and so their residence time decreases. Hypergravity decreases volumetric fraction of degassing bubbles and slightly their size. Final degree of liquid degassing does not change with hypergravity. Abstract: The formation and growth of bubbles due to decompression degassing of a liquid has been extensively studied in the past, aiming to enhance the efficiency of specific industrial applications. Even though liquid decompression degassing may interfere with the performance of space processes (such as cooling and lubrication systems, combustion and storage of liquid propellants etc.), the phenomenon has never been studied in non-terrestrial gravity conditions. The present work investigates for the first time, bubbles dynamics of a degassing liquid under various hypergravity accelerations. Degassing bubbles form due to desorption of dissolved air upon decompression of a liquid jet partially saturated with air. Accelerations up to 12 g are applied artificially by means of the Large Diameter Centrifuge facility of the European Space Agency. A patented electrical impedance spectroscopy technique provides the distribution of desorbed gas along the flow. Analysis of high resolution images indicates changes of bubbles size. Residence time distributions using conductivity tracers reveal the flow pattern in the degassing vessel. The total extent of liquid degassing is derived from dissolved oxygen measurements. Hypergravity alters the bubbles velocity and, consequently, their residence time in the liquid. Therefore, it affects the gas fraction in the degassing vessel offering unique conditions for studying the impact of acceleration on bubble dynamics. Experimental findings are useful not only for the optimization of space processes during hypergravity phases, e.g., space vehicles launch and re-orbiting, but also for the construction of controlled degassing industrial applications. Graphical abstract: Image, graphical abstract